The Mechanical Alignment of Dust (MAD): I. On the spin-up process of fractal grains by a gas-dust drift - Reißl, Stefan; Meehan, Paul; Klessen, Ralf S. (Arxiv, 2022)
Context: Aligned dust grains are commonly exploited to probe the magnetic field orientation. However, the exact physical processes that result in a coherent large-scale grain alignment are far from being constrained. Aims: In this work, we aim to investigate the impact of a gas-dust drift leading to a mechanical alignment of dust (MAD) and to dust polarization. Methods: We explore fractal dust aggregates to statistically analyze the average alignment behavior of distinct grain ensembles. The spin-up efficiencies for individual aggregates are determined utilizing MC simulations. These efficiencies are analyzed to identify stable points for the grain alignment in direction of the gas-dust drift and along the magnetic field lines. Finally, the net dust polarization is calculated per grain ensemble. Results: The mechanical spin-up within the CNM is sufficient to drive grains to a stable alignment. A likely mechanical grain alignment is parallel to the drift direction. Roundish grains require a supersonic drift while rod-like grains can align at subsonic conditions. Here, we predict a polarization efficiency in the order of unity for the MAD. A supersonic drift may result in a rapid rotation where dust grains may become rotationally disrupted and the polarization becomes drastically reduces. In the presence of a magnetic field the drift required for alignment is roughly one order of magnitude higher compared to the pure MAD. Here, the dust polarization efficiency is 0.8-0.9 indicating that a drift can provide the prerequisites to probe the magnetic field. The alignment is inefficient when the direction of the drift and the field lines are perpendicular. Conclusions: We find that MAD has to be taken into consideration as an alternative driving mechanism where the standard RAT alignment theory fails to account for the full spectrum of available dust polarization observations.